Measuring success of targeted screening and prevention for hemoglobinopathies - Agarwal, Rajat Kumar; Periyavan, Sundar; Trivedi, Deepa; Shah, Vaibhav; Reddy, Mohana; Mani, George; Sedai, Amit; Ankita, Kumari; Faulkner, Lawrence (Frontiers in Public Health, 2025)
Targeted screening for hemoglobinopathies is crucial for preventing affected births and mitigating the psychological and financial burdens on families. This study proposes two novel indicators—Screening index and prevention index—to evaluate the effectiveness of hemoglobinopathy prevention programs. The Screening index measures the proportion of at-risk women who are successfully screened and informed, while the Prevention Index assesses the number of women enrolled per birth prevented, reflecting the program’s efficiency in reducing affected births. These indicators account for critical factors such as counselor quality, testing accuracy, timeliness, accessibility, and demographic influences, which impact program success. We also address the limitations of traditional measures and emphasize the need for normalized indicators to adjust for variations in carrier rates across different populations. This approach enhances program monitoring, informs resource allocation, and guides improvements in screening and prevention strategies. Through these measures, we aim to provide a clear understanding of program outcomes, highlight areas for improvement, and offer a cost-efficient approach to prevent hemoglobinopathy-related births.